Biogenic CuO nanoparticles from Camellia sinensis and Pimpinella anisum plant extracts and their role as antimicrobial agents - André Paganotti; Carolina Cunha de Freitas; Roney H. Pereira; Vitor Gonçalves Vital; Giovanna S.M. Paiva; Lucas F. de Lima; Leonardo Longuini da Silva; Elizabeth Teodorov; Ricardo A. Galdino da Silva; Suzan Pantaroto de Vasconcellos; Amedea Barozzi Seabra (Plant Nano Biology)
Plant extracts have been successfully used to obtain nanoparticles with superior biological activity. This study assessed the biosynthesis, characterization, antimicrobial activity, and cytotoxicity of copper oxide nanoparticles (CuO NPs) synthesized using the extracts of green tea (Camellia sinensis) or anise seeds (Pimpinella anisum) as reducing and capping agents. These plant extracts presented significant concentrations of important phytochemicals, such as polyphenols and flavonoids. The biosynthesized nanoparticles were characterized by antioxidant capabilities, dynamic light scattering, high transmission electron microscope, thermogravimetric analysis, Fourier Transform Infrared Spectroscopy, X-ray diffraction and Uv-visible spectral analyses. Spherical nanoparticles with sizes of 11.31 ± 3.83 nm and 2.98 ± 0.44 nm using green tea and anise were obtained, respectively. Both the extracts and the biosynthesized particles presented antioxidant properties. The antimicrobial activity of both nanoparticles was evaluated against E. coli, S. aureus, P. aeruginosa, and C. albicans by determining the minimum inhibitory concentration (MIC) of the nanoparticles and their ability to disrupt the established biofilm of P. aeruginosa. Both nanoparticles demonstrated significant inhibitory effects, with MIC values of 31.25 µg/mL and 62.50 µg/mL against E. coli and S. aureus strains, respectively, and 15.62 µg/mL for the yeast. At the MIC concentration the nanoparticles inhibited 30 % of the bacterial cells of P. aeruginosa biofilm, and at higher concentrations, the CuO NPs achieved complete inhibition, i.e. more than 99 % of the cells. In these concentrations, the nanoparticles did not present significant cytotoxicity to mammal cells. These findings highlight the promising applications of both nanoparticles synthesized against resilient pathogens.